Analysis of the riveting process forming mechanisms. (4th August 2014) - Markiewicz, E.; Langrand, B.; Deletombe, E.; Drazetic, P.; Patronelli, L.
This paper deals with the characterisation of the residual stresses and strains due to the riveting process. In the first part, experimental results are given for two metal plate geometries and for three aspect ratios a/ø (edge margin/rivet shank diameter). As a result of this experimental investigation, a detailed analysis of forming and placing mechanisms is described for one rivet. Results show that the riveting process can be divided into seven distinct steps. The second part deals with the simulation capability by explicit FE codes, such as Pam–Solid™, to represent the local plastic flow along the riveting process. FEM results prove the numerical tool's ability to represent this complex forming process. FEM numerical tools can therefore optimize rivet designs more quickly and cheaply than experiments.